IbM PENGEMBANGAN UMKM LAMPU HIAS ELEMEN INTERIOR DI SURAKARTA - R. Ernasthan BS; Agung Purnomo (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Community service activities are aimed at improving the competitiveness of the assisted partners in facing the market development. Potential development of this decorative lamp product is still very open. Both partners both use solid waste raw materials from surrounding industries. The first partner is a craftsman Solo Batik KALINDA lamp that uses the main material waste of furniture production. The second partner is a craftsman Solo RAIHAN CRAFT Decorative lamps that use the remaining threads of textile industry. Both partners are located in the Surakarta municipality. Design limitations, human resources, business networks, and limited number and types of equipment cause poor partners to take advantage of the business development opportunities of the two craftsmen. After accompaniment, the partners are expected to be able to be a strong craftsman, so as to increase production, design, so as to increase family income, then more to absorb the labor that comes from the surrounding community environment. This community service activity is carried out over a period of ten months. The planned activities are; workshop design, workshop on the use of production tools with appropriate technology, simple management training, workshop on promotional materials and marketing. After getting a good touch of design, proper management, modernization of production tools, attractive promotional media is expected to increase the competitiveness of partners in the face of the market.